2010
DOI: 10.1111/j.1471-0528.2010.02694.x
|View full text |Cite
|
Sign up to set email alerts
|

Delivery outcome of women with epilepsy:a population‐based cohort study

Abstract: Please cite this paper as: Borthen I, Eide M, Daltveit A, Gilhus N. Delivery outcome of women with epilepsy: a population‐based cohort study.
BJOG 2010;117:1537–1543. Objective  To investigate whether women with epilepsy have increased risks of complications during labour, and to explore the impact of antiepileptic drug use. Design  Population‐based cohort study. Setting  Data from the Medical Birth Registry of Norway 1999–2005. Population  All births (n = 372 128) delivered in Norway, ensured through linkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 27 publications
(52 reference statements)
9
40
1
4
Order By: Relevance
“…This risk was higher when the women were using AEDs than when not taking AEDs. [10] For WWE without AED use, the risk of cesarean delivery is slightly increased but risk for any other complications is not considerably increased.…”
Section: Effect Of Epilepsy On Pregnancymentioning
confidence: 98%
See 1 more Smart Citation
“…This risk was higher when the women were using AEDs than when not taking AEDs. [10] For WWE without AED use, the risk of cesarean delivery is slightly increased but risk for any other complications is not considerably increased.…”
Section: Effect Of Epilepsy On Pregnancymentioning
confidence: 98%
“…Populationbased studies in Norway had revealed that infants exposed to AEDs in utero of mothers with epilepsy had lower Apgar score. [10] Teratogenic Effects…”
Section: Effect Of Epilepsy and Aed On Fetusmentioning
confidence: 99%
“…[30] Postpartum bleeding is a common cause of maternal mortality and anemia has been identified as one of the risk factors. [31] AED use during pregnancy has been associated with an increased tendency for postpartum bleeding;[4] and therefore, it is critical that anemia is monitored and treated adequately during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…[123] They have a higher frequency of pre-eclampsia, vaginal bleeding, and cesarean delivery. [134] As such, many may need continuous antiepileptic drug (AED) treatment during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Une étude récente [22] a montré que les femmes épileptiques avaient un faible taux de complications à l'accouchement mais néanmoins avaient un risque augmenté : d'accouchement dé clenché ; d'accouchement par cé sarienne ; d'hé morragie de la dé livrance. Cependant, il n'existe aucune recommandation pour préconiser chez la femme épileptique un accouchement déclenché ou par césarienne.…”
Section: Accouchementunclassified